Marine Collagen Matrix Carrier with Injectable Platelet-Rich Fibrin in Management of Gingival Recession Defects - Deepikha Krishnaraj; Harinath Parthasarathy; Anupama Tadepalli; Deepa Ponnaaiyan; A. Thirumal Raj; Shankargouda Patil; Snehashish Ghosh (Case Reports in Dentistry, 2023)
Background. The gold standard in the management of gingival recession (GR) defects has been connective tissue graft (CTG) with coronally advanced flap (CAF). But patient morbidity associated with graft harvesting is a major drawback and has led to the development of various substitute biomaterials which have been tried and tested. Aim. Our study is aimed at checking the efficacy of marine collagen matrix (MCM) impregnated with injectable platelet-rich fibrin (I-PRF) with modified CAF in the treatment of Miller’s class I and II recession defects. Case Description. Six patients with ten GR defects in maxilla were treated with CAF + MCM + I-PRF. Clinical parameters like recession height (RH), recession width (RW), root coverage (RC%), width of attached gingiva (WAG), keratinized tissue height (KTH), probing pocket depth (PPD), clinical attachment level (CAL), gingival biotype (GB), plaque index (PI), and visual analogue score (VAS-E) esthetic scores were evaluated up to six months. There was significant root coverage observed at three- and six-month follow-ups. Conclusion. The proposed treatment was effective in the management of GR defects and improvement in soft tissue biotype without the morbidity associated with soft tissue harvest.